Tackling Structure and Format -- The 'Great Unknown' in Professional Blogging - Owen Roberts; Jim Evans (Journal of Applied Communications, 2015)
This article addresses a gap in guidelines for those who blog professionally. It does so in a way that uniquely serves extension and research communicators. Many types of blogs have been used and described. Plenty of generic advice is available about writing blogs. However, little of it involves how to organize them. In this analysis, for example, advice about structure and format of blogs made up less than 3 percent of the 315 tips identified. A review of journalism literature identif ied some of the practices used in structuring news and information for media. The review also identified formats for organizing several other cousins of blogs. This article introduces a unique hybrid format for blogs, based on experiences of one of the authors. It involves a seven-step process that incorporates elements of objective reporting (explaining) with those of subjective expression (stimulating and advocating).
Keywords: Blogs; blogging; extension communications; research communications; writing skills